2019
DOI: 10.20473/cmsnj.v1i1.11967
|View full text |Cite
|
Sign up to set email alerts
|

Walking Exercise Programme (WEP) Menurunkan Cancer Related Fatigue (CRF) Pada Pasien Kanker Payudara Di RSUD. Ibnu Sina Gresik

Abstract: Introduction: Development of cancer and the side effect of chemotherapy could lead to Cancer Related Fatigue (CRF) in breast cancer patient that getting worse due to inactivation. Hence, exercise was needed. This aimed of this was to analyze the effect of Walking Exercise Program (WEP) to Cancer Related Fatigue.Methode: This study was used quasy experimental design and the population was breast cancer patient undergoing chemotherapy in RSUD Ibnu Sina Gresik in June 2012. The 10 respondents who met inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
0
0
4
Order By: Relevance
“…The result of this study is in line with the study Dieli found that physical exercise carried out with 3 times a week with a duration of 30 minutes per day in cancer patients found a decrease in fatigue level, the results of the study with p-value 0.002 (<0.05) shows the influence of physical exercise in the face of a decrease in fatigue level (18). This research is also in line with the research Wahyuni found that walking exercise program in breast cancer patients in IbnuSina Hospital reduced cancer-related fatigue with the results of the study with p-value 0.009 (<0.05) which showed that there is an effect of walking exercise in reducing fatigue (10) Doing physical exercise regularly and programmed, the immune system will increase. A good immune system will increase the number and function of Natural Killer cells which has a role as tumor suppression so that the risk of cancer decreases by recognizing and eliminating abnormal cells or through the innate or acquired immune system components.…”
Section: Discussionsupporting
confidence: 86%
“…The result of this study is in line with the study Dieli found that physical exercise carried out with 3 times a week with a duration of 30 minutes per day in cancer patients found a decrease in fatigue level, the results of the study with p-value 0.002 (<0.05) shows the influence of physical exercise in the face of a decrease in fatigue level (18). This research is also in line with the research Wahyuni found that walking exercise program in breast cancer patients in IbnuSina Hospital reduced cancer-related fatigue with the results of the study with p-value 0.009 (<0.05) which showed that there is an effect of walking exercise in reducing fatigue (10) Doing physical exercise regularly and programmed, the immune system will increase. A good immune system will increase the number and function of Natural Killer cells which has a role as tumor suppression so that the risk of cancer decreases by recognizing and eliminating abnormal cells or through the innate or acquired immune system components.…”
Section: Discussionsupporting
confidence: 86%
“…Menurut Yeo et all, (2012) menjelaskan bahwa dari berbagai efek pengobatan yang dirasakan klien, banyak pasien kanker lebih terganggu akibat timbulnya fatigue dari pada nyeri itu sendiri. 11 Potter dan Perry (2010) juga menjelaskan keluhan paling sering ditemui adalah rasa lelah akibat kanker/cancer related fatigue (CRF).…”
Section: Pembahasanunclassified
“…Beberapa faktor mempengaruhi tingkat fatigue yang berbedabeda pada tiap responden diantaranya faktor fisiologis seperti penyakit kanker itu sendiri, pengobatan kanker, nutrisi yang buruk (American cancer society, fatigue in people with cancer), pendidikan, kualitas tidur, nutrisi, pekerjaan, riwayat pola kebiasaan beserta durasinya, aktivitas seseorang serta kebiasaan exercise seseorang, serta faktor psikologis yang terdiri dari kecemasan, depresi, dan dukungan keluarga. 11 Pada saat melakukan wawancara pada kedua responden, didapatkan hasil bahwa dalam perjalanan penyakit yang diderita oleh kedua responden memiliki pengalaman emosional yang berbeda. Responden pertama mengatakan selama hampir dua tahun menderita kanker sudah hampir putus asa dikarenakan pengobatan yang dijalaninya dan merasa tidak ada harapan untuk sembuh, responden kedua mengalami stress selama menjalani pengobatan.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Uji statistik selanjunya untuk kontrol variabel perancu tetap mempertahankan efek signifikan WEP, di mana ditunjukkan WEP dapat memberikan efek 2,5 kali lebih besar dibanding kontrol (CI 2,039-3,041, p=0,001). Hasil penelitian ini sejalan dengan penelitian sebelumnya dimana ditunjukkan aktivitas fisik berjalan dapat menurunkan tingkat CRF secara signifikan 11,13 , meningkatkan kualitas hidup 14 , dan memperbaiki CRF pada pasien yang menjalani kemoterapi dan radioterapi. 8,15 Akan tetapi, tidak dianjurkan latihan fisik tanpa supervisi di mana meta analisis Velthus dkk.…”
Section: Diskusiunclassified